2020
DOI: 10.1021/acsaelm.0c00628
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Yb3+-Induced Phase Transition and Sensitized Luminescence in Er3+-Doped KNN-Based Lead-Free Ceramics for Optical Thermometry

Abstract: Environment-friendly potassium sodium niobate-based ferroelectrics have been widely and deeply studied for their electrical properties, but there remains much potential for applications in other fields, one of which is in optical temperature sensing. Herein, a host (K,Na)­Li0.04NbO3:0.5 mol% Er material with an orthogonal–tetragonal phase transition was constructed by Li+ regulation and then increased Yb2O3 codoping used to promote the occurrence of orthogonal to tetragonal and tetragonal to pseudocubic phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…The addition of 0.5% Er 2 O 3 significantly improved the ferro- and piezoelectric properties (i.e., due to the doping impact of the donor) of the ceramic synthesis and resulted in an intense photoluminescence. Additionally, the codoping of Er 3+ with Yb 2 O 3 greatly improved the upconversion intensity of the (K,Na)­Li 0.04 NbO 3 host material (as demonstrated in Figure and Figure ) when compared with only Er 3+ -doped samples …”
Section: Reos’ Optical Applications and Prospectsmentioning
confidence: 84%
See 3 more Smart Citations
“…The addition of 0.5% Er 2 O 3 significantly improved the ferro- and piezoelectric properties (i.e., due to the doping impact of the donor) of the ceramic synthesis and resulted in an intense photoluminescence. Additionally, the codoping of Er 3+ with Yb 2 O 3 greatly improved the upconversion intensity of the (K,Na)­Li 0.04 NbO 3 host material (as demonstrated in Figure and Figure ) when compared with only Er 3+ -doped samples …”
Section: Reos’ Optical Applications and Prospectsmentioning
confidence: 84%
“…Additionally, the codoping of Er 3+ with Yb 2 O 3 greatly improved the upconversion intensity of the (K,Na)Li 0.04 NbO 3 host material (as demonstrated in Figure 15 and Figure 16) when compared with only Er 3+ -doped samples. 124 In a different study, the Mg-borate glass properties were found to be sensitive to Dy 3+ concentrations. 125 The 0.7% Dy 3+ was hypersensitive at 1260 nm.…”
Section: Reos' Optical Applications and Prospectsmentioning
confidence: 96%
See 2 more Smart Citations